Win–win match using a genetic algorithm - Ayca, Altay; Gulgun, Kayakutlu; Y. Ilker, Topcu (Elsevier BV, 2010)
zbMATH Open Web Interface contents unavailable due to conflicting licenses.
Keywords: Matching models; Discrete location and assignment; Combinatorial optimization; matching problems; Modelling and Simulation; Applied Mathematics; conditional genetic algorithm; multi-functional decision making